Trabecular bone histomorphometry in humans with Type 1 Diabetes Mellitus - Armas, Laura A.G.; Akhter, Mohammed P.; Drincic, Andjela; Recker, Robert R. (Bone (New York, N.Y.), 2012)
Patients with Type 1 Diabetes Mellitus (DM) have markedly increased risk of fracture, but little is known about abnormalities in bone microarchitecture or remodeling properties that might give insight into the pathogenesis of skeletal fragility in these patients. We report here a case–control study comparing bone histomorphometric and micro-CT results from iliac biopsies in 18 otherwise healthy subjects with Type 1 Diabetes Mellitus with those from healthy age- and sex-matched non-diabetic control subjects. Five of the diabetics had histories of low-trauma fracture. Transilial bone biopsies were obtained after tetracycline labeling. The biopsy specimens were fixed, embedded, and scanned using a desktop μCT at 16μm resolution. They were then sectioned and quantitative histomorphometry was performed as previously described by Recker et al. [1]. Two sections, >250μm apart, were read from the central part of each biopsy. Overall there were no significant differences between diabetics and controls in histomorphometric or micro-CT measurements. However, fracturing diabetics had structural and dynamic trends different from nonfracturing diabetics by both methods of analysis. In conclusion, Type 1 Diabetes Mellitus does not result in abnormalities in bone histomorphometric or micro-CT variables in the absence of manifest complications from the diabetes. However, diabetics suffering fractures may have defects in their skeletal microarchitecture that may underlie the presence of excess skeletal fragility. ► We report a case–control study comparing bone histomorphometric and micro-CT results from iliac biopsies in Type 1 Diabetes Mellitus. ► There were no significant differences between diabetics and controls in histomorphometric or micro-CT measurements. ► However, fracturing diabetics had structural and dynamic trends different from nonfracturing diabetics by both methods of analysis.